Lemon Aromatherapy Intervention to Reduce Nausea and Vomiting in Gastritis Patients - Hamdani, Dadi; Rostantia, Beti; Sulistiani, Nendah; Hidayat, Nur (KIAN JOURNAL, 2022)
Objective: To present care with lemon aromatherapy intervention as an effort to overcome nausea and vomiting in gastritis patients. Methods: The method used is descriptive and uses nursing care that refers to the IDHS and SIKI books. The subject of this study was 1 patient with a nursing diagnosis of nausea and vomiting in gastritis patients who were treated in the Dahlia Room, Banjar City Hospital. Data collection includes interviews, observations, physical examinations and documentation. Results: The results of the case studies conducted showed a change after the non-pharmacological technique of lemon aromatherapy was proven by the final results, namely the evaluation carried out by the patient not feeling nauseated, the INVR scale 3. Conclusion: The conclusion from the results of the lemon aromatherapy intervention was considered effective for reducing nausea and vomiting with a decreased INVR scale. with the results of the final evaluation of the INVR 3 scale, the client said that nausea was reduced.